The Discourse of Noble Soul in Serat Kawruh Mahnitisme Manuscript - Septi Anggita Kriskartika; Titis Srimuda Pitana; Susanto Susanto (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2020)
This study aims at understanding and describing the discourse clarity, how the discourse is constructed and the implication of discursion of noble soul in sêrat kawruh mahnitismê manuscript in Javanese’s people life. The Sêrat Kawruh Mahnitismê will be written as SKM in this essay. This manuscript is in manuscript song form which consists of 13 pupuh ‘lyric’, and written using Javanese alphabet and in Javanese language that have been both translated and transcribed into Latin language. The manuscript is stored in Kerataon Surakarta Hadiningrat library Sasanapustaka containing teachings about how a person gets a perfection and used it as a tool to fulfill his dreams. This research is done in the area of Cultural Studies with qualitative data analysis and descriptive and interpretative analysis techniques that use a hermeneutic approach. This research use content analysis and library studies as method of data collection. The theory use is Michael Foucault discourse theory. The results show that: (1) the cause of discourse of noble soul in SKM manuscript that resulted hegemony; (2) the construction process in discourse of noble soul in SKM manuscript happens from ideal becomes humanist and (3) the implication of the discourse of noble soul in SKM manuscript in the millennial era